1968
DOI: 10.2134/agronj1968.00021962006000060004x
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mode of Action of Latex and Silicone Coatings on Shoot Growth and Water Use by Citrus1

Abstract: Coatings of latex and silicone were applied to potted sweet orange seedlings which were then grown either in the glasshouse or outside. Measurements of growth and moisture usage over a 20‐day period indicated that latex reduced moisture usage significantly in both situations. Growth was not significantly different for the treatment in any one environment. Leaf burn was less on latexcoated plants but distortion of the growing shoot appeared greater than in silicone‐coated and uncoated plants. Latex coatings app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1968
1968
1979
1979

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…The significant reduction of foliar chloride uptake by leaf coatings of L3 in experiment 4 supports the hypothesis that foliar uptake of chloride, and perhaps other ions, can be artificially reduced, Moreover, coatings which gave these encouraging results on mature citrus leaves kept in the glasshouse were 28 days old at the time of sprinkling, and may be assumed therefore to have good durability. The same films were found also to maintain their antitranspirant efficiency over the period of 28 days, and to exercise an insignificant effect on shoot growth in the glasshouse (Malcolm and Stolzy, 1968). Results for plants kept outside during the 28-day period are less encouraging, but still suggest benefits from L3-coating in terms of less chloride taken up.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The significant reduction of foliar chloride uptake by leaf coatings of L3 in experiment 4 supports the hypothesis that foliar uptake of chloride, and perhaps other ions, can be artificially reduced, Moreover, coatings which gave these encouraging results on mature citrus leaves kept in the glasshouse were 28 days old at the time of sprinkling, and may be assumed therefore to have good durability. The same films were found also to maintain their antitranspirant efficiency over the period of 28 days, and to exercise an insignificant effect on shoot growth in the glasshouse (Malcolm and Stolzy, 1968). Results for plants kept outside during the 28-day period are less encouraging, but still suggest benefits from L3-coating in terms of less chloride taken up.…”
Section: Discussionmentioning
confidence: 93%
“…But transpiration figures indicate that L3-coated leaves lost less water, and perhaps lowered permeability of the leaves to water vapor was also expressed in lowered chloride uptake. The degree to which film is not continuous (Malcolm and Stolzy, 1968) would influence its efficiency, and could be a factor in failure of other latex coatings to reduce chloride uptake. The significant increases in chloride level caused by latices L4 and L6 may be related to a com.bination of contact-angle lowering (perhaps due to surfactant) and faulty film formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marshall and Maki (1946) showed that pine seed lings dipped in lanolin or wax transpired forty percent less water than untreated seedlings over a four-day period. Latex was shovm to signif icantly reduce transpiration of potted orange trees over a twenty day period (Malcolm and Stolzy, 1968). They concluded that antitranspirants reduced transpiration by completely covering stomata or reducing stomatal pore size.…”
Section: Part II the Effects Of Antitranspirants On The Prevention Omentioning
confidence: 99%